Relationship of Helicobacter pylori Infection with Nonalcoholic Fatty Liver Disease: A Meta-Analysis - Guangqin Xu; Shaoze Ma; Liyan Dong; Nahum Mendez-Sanchez; Hongyu Li; Xingshun Qi (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Helicobacter pylori (H. pylori) and nonalcoholic fatty liver disease (NAFLD) have become increasingly recognized, both of which affect human health globally. The association of H. pylori infection with NAFLD remains unclear. Methods. PubMed, EMBASE, and Cochrane Library databases were searched. Only a random-effects model was used. Odds ratios (ORs) and risk ratios (RRs) with 95% confidence intervals (CIs) were calculated for the combined estimates of raw data. Adjusted ORs (aORs) and hazard ratios (aHRs) with 95% CIs were calculated for the combined estimates of data adjusted for confounders. Results. Thirty-four studies with 218573 participants were included. Based on unadjusted data from 26 cross-sectional studies and 3 case-control studies, H. pylori infection was significantly associated with the presence of NAFLD (OR = 1.26, 95% CI = 1.17–1.36, P<0.001). Based on adjusted data from 15 cross-sectional studies and 1 case-control study, H. pylori infection was significantly associated with the presence of NAFLD (aOR = 1.25, 95% CI = 1.08–1.44, P<0.001). Compared with control subjects without NAFLD, patients with moderate (OR = 1.67, 95% CI = 1.17–2.39, P=0.005) and severe (OR = 1.71, 95% CI = 1.30–2.24, P<0.001) NAFLD, but not those with mild NAFLD (OR = 1.14, 95% CI = 0.9–1.45, P=0.286), had significantly higher proportions of H. pylori infection. The association of H. pylori infection with the occurrence of NAFLD was statistically significant based on adjusted data from 3 cohort studies (aHR = 1.18, 95% CI = 1.05–1.34, P=0.007), but not based on unadjusted data from 3 cohort studies (RR = 1.41, 95% CI = 0.80–2.48, P=0.237). Conclusion. H. pylori infection is associated with NAFLD, especially moderate and severe NAFLD. The impact of H. pylori eradication on the prevention of NAFLD should be further explored.